Combined Prophylaxis with Uterotonics and Tranexamic Acid for Intrapartum Postpartum Hemorrhage (PPH): Hemostatic, Pharmacologic, Cardiac, and Anesthetic Considerations by Risk Category — A Decade Review of Randomized Controlled Trials - Dr. Muniba Ali,Dr. Aisha Ali,Dr. Nimra Samad,Dr. Syed Shayan Ahmed,Dr. Syed Hasnain Mujtaba,Dr. Pavan Kumar,Dr. Amber Shams (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Postpartum hemorrhage (PPH) remains the leading direct cause of maternal mortality worldwide, with uterine atony accounting for nearly 70% of cases. Conventionalprophylaxis relies on uterotonics